Organizational Risk Management Model:Systematic Evaluation of Effective Approaches and Methods - Abdul Ghofur (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to analyze the factors that influence the effectiveness of organizational riskmanagement models through a Systematic Literature Review (SLR) approach. Variousreference sources from international databases have been analyzed to identify internal andexternal factors that influence risk management, including organizational culture, organizationalstructure, leadership, risk identification, analysis and response processes, as well as technologyand resource related factors. The research results show that integration and a deepunderstanding of these factors are critical to developing an effective organizational riskmanagement model. By considering and integrating these factors, organizations can improvetheir ability to better manage risk and achieve their goals amidst existing uncertainty.